2008
DOI: 10.1017/s0266466608080614
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Autoregressive Conditional Correlation

Abstract: This paper develops a generalized autoregressive conditional correlation~GARCC! model when the standardized residuals follow a random coefficient vector autoregressive process+ As a multivariate generalization of the Tsay~1987, Journal of the American Statistical Association 82, 590-604! random coefficient autoregressive~RCA! model, the GARCC model provides a motivation for the conditional correlations to be time varying+ GARCC is also more general than the Engle~2002, Journal of Business & Economic Statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 147 publications
(155 citation statements)
references
References 23 publications
3
152
0
Order By: Relevance
“…Corollary 4 is consistent with the proof in McAleer et al (2008) that the QMLE of Full BEKK has no asymptotic properties, whereas the QMLE of Diagonal BEKK can be shown to be consistent and asymptotically normal.…”
Section: Corollarysupporting
confidence: 85%
See 1 more Smart Citation
“…Corollary 4 is consistent with the proof in McAleer et al (2008) that the QMLE of Full BEKK has no asymptotic properties, whereas the QMLE of Diagonal BEKK can be shown to be consistent and asymptotically normal.…”
Section: Corollarysupporting
confidence: 85%
“…In short, can be related directly to the data, , using equations (1) and (2). Ling and McAleer (2003) and McAleer et al (2008) provide general proofs of the asymptotic properties of univariate and multivariate conditional volatility models based on satisfying the regularity conditions in Jeantheau (1998) for consistency, and in Theorem 4.1.3 in Amemiya (1985) for asymptotic normality.…”
Section: Univariate Conditional Volatility Modelsmentioning
confidence: 99%
“…For further details, see Ling and McAleer (2003) and McAleer et al (2008), who provide general proofs of the asymptotic properties of multivariate conditional volatility models based on satisfying the regularity conditions in Jeantheau (1998) for consistency, and in Theorem 4.1.3 in Amemiya (1985) for asymptotic normality.…”
Section: Advances In Economics Business and Management Research (Aebmentioning
confidence: 99%
“…In the case where A is a diagonal matrix, with a ii > 0 for all i = 1, ...., m, and | b ij |< 1| for all j = 1, ...., m, so that A has dimension m × m, McAleer et al [10] showed that the multivariate extension of GARCH(1,1) from equation (5) is given as the Diagonal BEKK model, namely:…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in McALeer et al [10] that the QMLE of the parameters of the DBEKK model are consistent and asymptotically normal, so that standard statistical inference for testing hypotheses is valid. However, Chang and McAleer [4] demonstrate that this is not the case for the Full BEKK model.…”
Section: Introductionmentioning
confidence: 99%